2021
DOI: 10.1126/sciadv.abd7658
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the severity of the grass pollen season and the effect of climate change in Northwest Europe

Abstract: Allergic rhinitis is an inflammation in the nose caused by overreaction of the immune system to allergens in the air. Managing allergic rhinitis symptoms is challenging and requires timely intervention. The following are major questions often posed by those with allergic rhinitis: How should I prepare for the forthcoming season? How will the season’s severity develop over the years? No country yet provides clear guidance addressing these questions. We propose two previously unexplored approaches for forecastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…In some instances, during thunderstorm activity, pollen can burst into hundreds of sub-pollen particles of paucimicronic size, causing a phenomenon called “thunderstorm asthma” (TA). Scientists predict that climate change will increase the concentration of airborne pollen, as the frequency and intensity of rainfall is also likely to increase [ 18 , 19 ]. As a result, the prevalence and severity of pollen-induced asthma, AR and sensitisation are also expected to increase [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some instances, during thunderstorm activity, pollen can burst into hundreds of sub-pollen particles of paucimicronic size, causing a phenomenon called “thunderstorm asthma” (TA). Scientists predict that climate change will increase the concentration of airborne pollen, as the frequency and intensity of rainfall is also likely to increase [ 18 , 19 ]. As a result, the prevalence and severity of pollen-induced asthma, AR and sensitisation are also expected to increase [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Daepp et al (2001) showed that the effects of elevated CO 2 will depend on the developmental stage of the ryegrass, suggesting that some stages are more sensitive to than others. For grasses in general, elevated CO 2 has been suggested to intensify the reproductive period from increases in NPP (Kurganskiy et al, 2021). Climate change will lead to multiple changes in the environment: increased temperature and CO 2 may have positive effects by extending the growing season for certain species while simultaneously flooding or drought may have negative effects on overall plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…This is another aspect of high CO 2 and stress combination that needs to be addressed, particularly in light of the potential negative effects of stress combinations on NUE. Because the breath of high CO 2 effects on crops is too vast to cover here, the reader is directed to several excellent reviews on the subject (Ainsworth and Long, 2021;Bright and Lund, 2021;Delabre et al, 2021;Green et al, 2020;Kurganskiy et al, 2021;Lamichaney and Maity, 2021;Lu et al, 2020;Penuelas et al, 2020;Schmidt et al, 2021;Smith, 2021;Soh et al, 2019;Tausz-Posch et al, 2020;Toreti et al, 2020;Wang and Liu, 2021;Wang et al, 2020;Xu et al, 2020).…”
Section: Stress Combination In a High Co 2 Environmentmentioning
confidence: 99%